Breast Tissue Chemistry Measured In Vivo In Healthy Women Correlate with Breast Density and Breast Cancer Risk. Issue 5 (13th October 2022) - Santamaría, Gorane; Naude, Natali; Watson, Julia; Irvine, John; Lloyd, Thomas; Bennett, Ian; Galloway, Graham; Malycha, Peter; Mountford, Carolyn
Abstract : Representative two‐dimensional correlated spectroscopy (2D COSY) spectra of the region F2/F1: 0.00 ppm to 6.00 ppm in participants at low risk. (a ) low dense tissue and premenopausal status (30 years old), (b ) low dense tissue and postmenopausal (54 years old), (c ) high dense tissue and premenopausal (36 years old), and (d ) high dense tissue and postmenopausal (66 years old). Note the increase in intensity for cross peaks F, D, G, and G′ across categories. By Gorane Santamaría et al. (1355–1369)